2014
DOI: 10.4012/dmj.2013-274
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of temperature changes in the pulp chamber during polymerization of light-cured pulp-capping materials by using a VALO LED light curing unit at different curing distances

Abstract: The aim of this study was to evaluate temperature changes in the pulp chamber during polymerization of four different pulp-capping materials using a LED-light-curing-unit in the contact and noncontact positions. A pulpal circulation mechanism was simulated to measure increases in temperature in four pulp-capping materials that were applied to the occlusal dentin surface. Two different distances were used between the tip of the unit and the material surface during polymerization; 0 and 2 mm. The data were stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 34 publications
2
67
0
6
Order By: Relevance
“…The sample size was calculated at a 95% confidence interval and a significance level of 0.05 (effect size=1.37), according to the study by Savas et al 29) . Although their data suggested that a total of 21 specimens would be adequate for analysis, a worstcase scenario was proposed, with an effect size of 0.6.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size was calculated at a 95% confidence interval and a significance level of 0.05 (effect size=1.37), according to the study by Savas et al 29) . Although their data suggested that a total of 21 specimens would be adequate for analysis, a worstcase scenario was proposed, with an effect size of 0.6.…”
Section: Methodsmentioning
confidence: 99%
“…The intrapulpal temperature changes during the curing/setting of the bulk-fill restorative materials were determined with a device that simulated pulpal blood microcirculation [28][29][30] . This device consisted of a fixed mechanism providing the circulation of distilled water, at room temperature, with a flow rate of 0.026 mL per min, in the pulp chamber of the specimens 31) .…”
Section: Methodsmentioning
confidence: 99%
“…Outro fator que pode influenciar o aumento de temperatura intra câmara pulpar é a espessura da dentina remanescente e, no presente estudo, a mesma foi padronizada em 1mm (Pameijer et al, 1991;Hannig e Bott, 1999;Daronch et al, 2007;Choi et al, 2014;Savas et al, 2014), simulando uma situação clínica crítica de cavidade profunda. A aferição desta feita através do especímetro inserido na câmara pulpar e na parte vestibular, metodologia esta utilizada também por Martins et al (2006).…”
Section: Variação Da Temperatura Intra Câmara Pulpar Em Função Das Founclassified
“…Desta forma, a ponta das fontes de luz foi posicionada em contato com uma tira de poliéster apoiada na superfície, com o intuito de simular uma situação crítica. Savas et al, (2014), posicionaram a ponta do aparelho fotopolimerizador de luz visível sobre as resinas, encostando-se à tira matriz de poliéster que as protegia e ativando-as por 20, 40 e 60s . Outros autores defendem que não é prudente colocar fontes de luz com alta intensidade em contato direto com o substrato dentinário (Loney e Price, 2001).…”
Section: Variação Da Temperatura Intra Câmara Pulpar Em Função Das Founclassified
See 1 more Smart Citation